Insular pathways to health care in the city: a multilevel analysis of access to hospital care in urban Kerala, India - Jean-Fre'de' ric Levesque, Slim Haddad, Delampady Narayana and Pierre Fournier (Tropical Medicine and International Health volume 12 no 7 pp 802-814 july 2007, 2007)
To identify individual and urban unit characteristics associated with access to inpatient care in public and private sectors in urban Kerala, and to discuss policy implications of inequalities in access. methods We analysed the NSSO survey (1995-1996) for urban Kerala with regard to source and trajectories of hospitalization. Multinomial multilevel regression models were built for 695 cases nested in 24 urban units. results Private sector accounts for 62 per cent of hospitalizations. Only 31 of hospitalizations are in free wards and 20 of public hospitalizations involve payment. Hospitalization pathways suggest a segmentation of public and private health markets. Members of poor and casual worker households have lower propensity of hospitalization in paying public wards or private hospitals. There were important variations between cities, with higher odds of private hospitalization in towns with fewer hospital beds overall and in districts with high private-public bed ratios. Cities from districts with better economic indicators and dominance of private services have higher proportion of private hospitalizations. conclusions The private sector is the predominant source of inpatient care in urban Kerala. The public sector has an important role in providing access to care for the poor. Investing in the quality of public services is essential to ensure equity in access